Accidental hanging in an eight-year old child - Ray, Sandip; Meena, Sangeeta; Patra, Bijoy (International Journal of Contemporary Pediatrics, 2016)
Accidental hanging in children, although uncommon, has been reported worldwide. We report a case of an eight-year-old female who was brought to our hospital with an alleged history of hanging with his head trapped in-between the ropes of a cot. She became unconscious and developed seizures secondary to asphyxial injury and survived. Hanging is an important cause of homicidal and suicidal injury in adults, but in children, it is usually accidental, leading to death because of asphyxia as a result of partial or complete hanging. There is paucity of data in Indian literature regarding accidental hanging injuries in children. According to available data from western countries, strangulation ranks fourth among the causes of unintentional injury in children. The unique mode of hanging in this child has prompted us to report this case.